Detection of the de novo Pro253Arg Mutation of Fibroblast Growth Factor Receptor 2 (FGFR2) in a Pediatric Patient with Congenital Hand Anomaly - Ngoc, Nguyen Thy; Duc, Hoang Hai (VNU Journal of Science: Natural Sciences and Technology, 2023)
Congenital hand deformities are a group of birth defects related to abnormal development of soft, cartilage, or bone tissues in the hands. Recent studies have indicated that the most usual reason of congenital hand anomalies are due to the genetic factors. In this study, we sequenced the exome of a 2.5-year-old female patient case with bilateral hand deformity. Results revealed that the patient did not carry mutations in the expression region of the GLI3 and SHH genes. However, the patient did have a heterozygous mutation: FGFR2 : c.C758G, p.P253R. Sanger sequencing confirmed this was a de novo mutation as it was not detected in her parents. In silico analyses indicated that P253R has a potential effect to alter the structure and function of the fibroblast growth factor receptor, consequently disrupting the processes involved in the formation and development of bone and cartilage tissues. Overall, this research will contribute to a better understanding of the role and functionality of the FGF molecular signaling network in the development and synthesis of bone and cartilage tissues, particularly during the embryonic stage.